Maatalouden ympäristötuen perustuen merkitys maatilojen taloudelle - Koikkalainen, Kauko; Haataja, Kaisu; Aakkula, Jyrki (Maatalouden taloudellinen tutkimuslaitos, 1999)
Agri-environmental support included in the General Agri-Environmental Protection Scheme (GAEPS) is used to compensate the farmers for the loss of farm income and increased production costs due to the adaptation of more environmentally-friendly production practices. This study is an attempt to estimate and aggregate the costs of the GAEPS. The main costs at the farm level consist of investments to manure and silage storage, crop losses due to reduced use of nitrogen and phosphorus fertilisers, and landscape management. Other major sources of additional costs are the plant cover criterion, regular soil fertility testing, and nutrient analyses of manure. Filter strips, testing of pesticide sprayers, and making an environmental management plan for the farm are also cost-creating activities. According to the calculations, the total cost of the adaptation of the GAEPS are ca. FIM 850 million annually. This corresponds to the a priori cost estimates that were made at the planning stage of the GAEPS. In addition, farm models were used to assess the monetary net benefits of the GAEPS in different types of farms. It seems that the GAEPS has the most significant effect on net farm income in the southern part of Finland.
Keywords: Ma; ympäristötuki; maatalous; maatilatalous; agriculture; environmental support; agri-environmental programme; farm economy